A Quantile Analysis of Plateau and Driving Pressures: Effects on Mortality in Patients With Acute Respiratory Distress Syndrome Receiving Lung-Protective Ventilation*. Issue 5 (May 2017) - Villar, Jesús; Martín-Rodríguez, Carmen; Domínguez-Berrot, Ana M.; Fernández, Lorena; Ferrando, Carlos; Soler, Juan A.; Díaz-Lamas, Ana M.; González-Higueras, Elena; Nogales, Leonor; Ambrós, Alfonso; Carriedo, Demetrio; Hernández, Mónica; et al.
Abstract : Objectives: The driving pressure (plateau pressure minus positive end-expiratory pressure) has been suggested as the major determinant for the beneficial effects of lung-protective ventilation. We tested whether driving pressure was superior to the variables that define it in predicting outcome in patients with acute respiratory distress syndrome. Design: A secondary analysis of existing data from previously reported observational studies. Setting: A network of ICUs. Patients: We studied 778 patients with moderate to severe acute respiratory distress syndrome. Interventions: None. Measurements and Main Results: We assessed the risk of hospital death based on quantiles of tidal volume, positive end-expiratory pressure, plateau pressure, and driving pressure evaluated at 24 hours after acute respiratory distress syndrome diagnosis while ventilated with standardized lung-protective ventilation. We derived our model using individual data from 478 acute respiratory distress syndrome patients and assessed its replicability in a separate cohort of 300 acute respiratory distress syndrome patients. Tidal volume and positive end-expiratory pressure had no impact on mortality. We identified a plateau pressure cut-off value of 29 cm H2 O, above which an ordinal increment was accompanied by an increment of risk of death. We identified a driving pressure cut-off value of 19 cm H2 O where an ordinal increment was accompanied by an increment of risk of death. When we cross tabulated patients with plateau pressure less than 30 and plateau pressure greater than or equal to 30 with those with driving pressure less than 19 and driving pressure greater than or equal to 19, plateau pressure provided a slightly better prediction of outcome than driving pressure in both the derivation and validation cohorts ( p < 0.0000001). Conclusions: Plateau pressure was slightly better than driving pressure in predicting hospital death in patients managed with lung-protective ventilation evaluated on standardized ventilator settings 24 hours after acute respiratory distress syndrome onset. Abstract : Supplemental Digital Content is available in the text.